The Relationship Between Motivation and Perceived Parental Encouragement for Learning English as a Foreign Language with English Achievement of Grades 6 to 8 Students at St. John’s Private School, Pathein, Myanmar - Marina, Nant; Eamoraphan, Suwattana (Scholar: Human Sciences, 2020)
The purpose of the study was to determine the relationship between motivation and perceived parental encouragement for learning English as a foreign language with English achievement of Grades 6 to 8 students at St. John’s Private School, Pathein, Myanmar. The study was quantitative study, and motivation questionnaire was used to collected data from 157 students in academic year 2018-2019 at St. John’s Private School, Pathein, Myanmar. For English achievement test, Grades 6 to 8 monthly test was used in this study. Means, standard deviations, and Pearson correlation coefficient were used to analyze the data. The findings showed that students’ motivation for learning English as a foreign language was interpreted as very high, and perceived parental encouragement for learning English as a foreign language was very high as well. The final finding of this study showed that there was no significant between perceived parental encouragement and English achievement at Grades 6 to 8 students at St. John’s Private School, Pathein. Myanmar.